THE THEMATIC FIELD WITH THE FEATURE “DEVIATION FROM THE NORM” IN THE RUSSIAN LANGUAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the thematic field with the feature “deviation from the norm” in the Russian language as an important component of the lexical-semantic system. It represents a structured set of evaluative lexical units reflecting cultural values, social expectations, and collective notions of normality. The analysis shows that deviation from the norm is conceptualized through metaphor, expressive word-formation, and evaluative semantics. The main lexical-semantic groups, their negative connotation, and pragmatic orientation are identified.